2021
DOI: 10.1002/adma.202008715
|View full text |Cite
|
Sign up to set email alerts
|

Nanoengineered Peptide‐Based Antimicrobial Conductive Supramolecular Biomaterial for Cardiac Tissue Engineering

Abstract: Owing to their dynamic nature and ordered architecture, supramolecular materials strikingly resemble organic components of living systems. Although short‐peptide self‐assembled nanostructured hydrogels are regarded as intriguing supramolecular materials for biotechnology, their application is often limited due to their low stability and considerable challenge of combining other desirable properties. Herein, a di‐Fmoc‐based hydrogelator containing the cell‐adhesive Arg–Gly–Asp (RGD) fragment that forms a mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 59 publications
2
68
0
Order By: Relevance
“…This positive effect of RGD in cell cultures is not surprising, since it is known to be a promoter of cell adhesion. 25 , 47 Regarding the role of MNP and in agreement with our results for peptide hydrogels, several previous studies reported that when MNP are added to polymeric scaffolds for tissue engineering applications, they stimulate adhesion, proliferation, and differentiation of cells in vitro and even bone formation in vivo. 48 50 In the present work, differences between cell proliferation in different samples correlated well with differences in mechanical properties: Stronger hydrogels (higher G ′) connected with larger numbers of cells at a given cell culture period.…”
Section: Resultssupporting
confidence: 89%
“…This positive effect of RGD in cell cultures is not surprising, since it is known to be a promoter of cell adhesion. 25 , 47 Regarding the role of MNP and in agreement with our results for peptide hydrogels, several previous studies reported that when MNP are added to polymeric scaffolds for tissue engineering applications, they stimulate adhesion, proliferation, and differentiation of cells in vitro and even bone formation in vivo. 48 50 In the present work, differences between cell proliferation in different samples correlated well with differences in mechanical properties: Stronger hydrogels (higher G ′) connected with larger numbers of cells at a given cell culture period.…”
Section: Resultssupporting
confidence: 89%
“…Fourier‐transform infrared spectroscopy spectra of Gel 5 exhibited two bands in the Amide I region (Figure S3, Supporting Information) at 1687 and 1636 cm −1 which may indicate an antiparallel β ‐sheet‐like signature. [ 23 ] Gel 4 exhibited a peak at 1700 cm −1 which may be ascribed to the C═O vibrations of the amide group [ 57,58 ] that shifted to 1688 cm −1 in the co‐assembled gels indicating its participation in H‐bonding during co‐assembly. Intriguingly, the antiparallel β ‐sheet‐like signature of Gel 5 remained intact in Gel 1, Gel 2, and Gel 3, demonstrating that Fmoc‐K(Fmoc)‐RGD conferred its secondary structure to the co‐assembled gels.…”
Section: Resultsmentioning
confidence: 99%
“…The components were dissolved in phosphate-buffered saline (PBS) under constant stirring at 40 °C. Based on a previous study, 31 hydrogels possess immense potential for mimicking the extracellular matrix (ECM) owing to their ability to introduce bioactive factors by simple physical mixing. SDSSD (synthesized by Shanghai Pingyao, China) was added by simple physical mixing to S3G7H5 as the experimental group and S3G7H5 as the control group.…”
Section: Methodsmentioning
confidence: 99%